The Accuracy of Forecasts: A Market Equilibrium Analysis - Pashigian, B. Peter (Quarterly Journal of Economics, 1974)
Some features of the theory 86. — Expected profits of the firm, 88. — Optimal accuracy of forecasts, 91. — Market equilibrium, 92. — Comparative statics, 92. — Conclusion, 96.